The cytidine deaminase signature HxE(x)nCxxC of DYW1 binds zinc and is necessary for RNA editing of ndhD‐1. Issue 4 (10th July 2014) - Boussardon, Clément; Avon, Alexandra; Kindgren, Peter; Bond, Charles S.; Challenor, Michael; Lurin, Claire; Small, Ian
Summary In flowering plants, RNA editing involves deamination of specific cytidines to uridines in both mitochondrial and chloroplast transcripts. Pentatricopeptide repeat (PPR) proteins and multiple organellar RNA editing factor (MORF) proteins have been shown to be involved in RNA editing but none have been shown to possess cytidine deaminase activity. The DYW domain of some PPR proteins contains a highly conserved signature resembling the zinc‐binding active site motif of known nucleotide deaminases. We modified these highly conserved amino acids in the DYW motif of DYW1, an editing factor required for editing of the ndhD‐1 site in Arabidopsis chloroplasts. We demonstrate that several amino acids of this signature motif are required for RNA editing in vivo and for zinc binding in vitro. We conclude that the DYW domain of DYW1 has features in common with cytidine deaminases, reinforcing the hypothesis that this domain forms part of the active enzyme that carries out RNA editing in plants.